Gender Inequality in Employment in Mozambique. (29th April 2019) - Gradín, Carlos; Tarp, Finn
Abstract: We investigate the gender employment gap in the expanding non‐subsistence sector of the economy in Mozambique, a country still characterized by a large subsistence agricultural sector. We show evidence that the gender gap has widened over time and we identify two structural factors strongly associated with it. One factor is the still relatively lower level of female human capital, with less attained education, as well as literacy and Portuguese proficiency rates. The lower conditional employment probabilities of married women, as compared with men, is the other factor. These findings point at expanding women´s education and facilitating the access of married women to the emerging labour market as the most effective ways of achieving a more inclusive growth path that does not leave women behind.